Organizational culture and the individuals' discretionary behaviors at work: a cross-cultural analysis - Fernandes, Pedro; Pereira, Rúben; Wiedenhöft, Guilherme (Frontiers in Sociology, 2023)
Stating ‘how things are done here,’ organizations are defining their culture. Organizational Culture (OC) is the set of values, norms, goals, and expectations shared by all members of an organization that aids in improving their commitment and performance. On the organizational level, it impacts behavior, productivity, and long-term survival by influencing organizational capability. Due to employee behavior being a competitive differential, this study examines how specific OCs influence individual behavior. In particular, how the different cultures in the OCAI model affect employees’ main dimensions of Organizational Citizenship Behavior (OCB). A descriptive-confirmative ex post facto research was conducted by surveying 513 employees from over 150 organizations worldwide. The Kruskal-Wallis H test was used to validate our model. The general hypothesis was confirmed, showing that the predominant organizational culture type affects the level and the kind of OCBs individuals demonstrate. It is possible to provide organizations with a breakdown of their employees’ OCBs based on their OC type and which changes they can make to their organization’s culture to increase the employees’ OCB and, consequently, the efficiency of their organization.